FAK and paxillin, two potential targets in pancreatic cancer - Kanteti, Rajani (Oncotarget, 2016)
Pancreatic ductal adenocarcinoma (PDAC) is a devastating cancer in large part due to late diagnosis and a lack of effective screening tests. In spite of recent progress in imaging, surgery and new therapeutic options for pancreatic cancer, the overall five-year survival still remains unacceptably low. Numerous studies have shown that focal adhesion kinase (FAK) is activated in many cancers including PDAC and promotes cancer progression and metastasis. Paxillin, an intracellular adaptor protein that plays a key role in cytoskeletal organization, connects integrins to FAK and plays a key role in assembly and disassembly of focal adhesions. Here, we have reviewed evidence in support of FAK as a potential therapeutic target and summarized related combinatorial therapies.